Self-as-object and self-as-subject in the workplace - Brockner, Joel; Wiesenfeld, Batia M. (Organizational behavior and human decision processes, 2016)
•The self exerts influence at work as object (as a target of reflected appraisal).•The self also exerts influence as subject, e.g., by maintaining executive control.•The distinction between the two sheds light on numerous areas in micro-OB.•These areas include motivation, organizational change, ethics, and justice. Drawing on James’s (1890) age-old distinction between the “Me-self” and the “I-self,” we discuss the implications of two self-processes (self-as-object and self-as-subject, respectively) for organizational behavior. The self-as-object is primarily concerned with thinking about oneself in valued ways, whereas the self-as-subject is primarily concerned with behavioral self-regulation. Using two prominent self-theories (self-affirmation, a self-as-object framework) and ego depletion theory (a self-as-subject perspective), we first show how results across disparate literatures in organizational behavior may be accounted for by common underlying mechanisms, and the advances that emerge from recognizing this convergence. We then consider a variety of ways in which insights into organizational behavior may be gleaned from examining the self-as-object and self-as-subject conjointly. Processes associated with the self-as-object and self-as-subject combine interactively to influence employees’ attitudes and behavior, and they also influence one another. Furthermore, considering the two self-processes in tandem shows how: (1) effects that appear to be similar differ meaningfully in the mechanisms accounting for them, and (2) seemingly discrepant results may be reconciled. Our analysis demonstrates that the two self-processes have implications for many literatures in organizational behavior including motivation, organizational change, ethics, justice, escalation of commitment, social identity, control, and power. Suggestions for future research and managerial implications also are provided.